An overview of the role of long non-coding RNAs in human choriocarcinoma - Di Fiore, Riccardo (2021)
Funding: The publication of this manuscript was funded by the European Cooperation in Science & Technology Program (EU COST)–COST Action CA18117: GYNOCARE- “European network for Gynaecological Rare Cancer research: From Concept to Cure”. R.D.F., S.S., A.F., S.A.O., J.J.O., M.P.W., J.B., M.S., P.O., A.Y., M.V.-S., B.E., A.G., and J.C.-A. are Action management committee members and/or form part of Working Groups 1–3, and J.C.-A. is the Chairperson of this Action.